PENGEMBANGAN KOMPETENSI SOSIAL OLEH GURU DALAM MENINGKATKAN PROSES PEMBELAJARAN - Dian Novita Malasri; Enas Enas; Maman Herman; Asep Budi Tauhid (LPPM Universitas Muhammadiyah Bulukumba, 2024)
This research focuses on the problem of developing teachers' social competence in improving the learning process, this is motivated by various problems about the quality of teaching, especially at the early childhood education level. This research was conducted through descriptive methods with a qualitative approach, and technically is a case study research at Anandita Kindergarten, Klapanunggal sub-district, Bogor Regency. Through data collection techniques of interviews, observation and documentation, then a number of data are processed through steps: data display, data reduction and data analysis and supported by time triangulation, expert confirmation and repetition of the process. This research resulted in the following conclusions: (1) the social competence of teachers in improving the learning process at Anandita Kindergarten can be categorized as good, supported by efforts to develop the social competence of teachers by the Head of Kindergarten. (2) The obstacles that are still faced by teachers come from the weaknesses of school management, such as: weak learning support facilities, weak school budgets that have an impact on all sectors of financing, and management of cooperation and coordination between school parties and stakeholders such as the community and parents of students; (3) Strategies for developing teachers' social competencies at Anandita Kindergarten include: indirect direct coaching strategies from the head of Anandita Kindergarten, independent personal development of teachers, strategies for strengthening internal TK managerial, strategies for implementing certain innovations, strategies for strengthening internal cooperation, and strategies for strengthening external cooperation.